EVALUATION OF THE APPLICABILITY OF DRONE-GENERATED PRODUCTS AS SUPPORT FOR MINERAL PROSPECTING AND EXPLORATION: CASE STUDY IN THE REGION OF NOVA LIMA – MINAS GERAIS - Borges, Gabriele Santiago; de Magalhães, Danilo Marques [UNESP] (UNESP - Universidade Estadual Paulista, 2024)
Remotely Piloted Aircraft (RPA), popularly known as Drones, have been widely used in mining, whose competitive scenario requires operational performance optimization combined with attractive costs. Aiming to understand how an RPA can assist in carrying out studies in mineral prospecting and exploration, this study used this tool to perform an aerial survey in an area with potential for iron ore exploration, located in the Quadrilátero Ferrífero, Minas Gerais. The objective was to evaluate the products generated by a consumer-grade drone as support for mineral prospecting. Specifically, the aim was to assess whether these products favor a better and more assertive geological and geomorphological characterization of the region, when compared to the available spatial data, in the context of mineral prospecting and exploration. For this, an Orthomosaic, Digital Terrain Model (DTM), and Textured 3D Model were generated. The results allowed for the identification of the main geological and geomorphological features with greater clarity and, therefore, the drone proved to be an interesting complementary tool for prospecting and mineral exploration work, highlighting efficiency gains and competitive costs to conventional field surveys.
AVALIAÇÃO DA APLICABILIDADE DOS PRODUTOS GERADOS POR DRONE COMO SUPORTE À PROSPECÇÃO E EXPLORAÇÃO MINERAL: ESTUDO DE CASO EM UMA SEÇÃO NA REGIÃO DE NOVA LIMA – MINAS GERAIS
Keywords: Aerial Survey; Drone; Mineral prospecting and exploration; RPA